1975
DOI: 10.1161/01.res.36.6.28
|View full text |Cite
|
Sign up to set email alerts
|

A circulating renin activator in essential hypertension.

Abstract: The rate of angiotensin generation with added renin in plasma from patients with benign essential hypertension has been shown to be higher than in plasma from norm ensive controls. An index of the angiotensin generation rate in relation to to al plasma renin substrate (PRS-r index) has been defined which allows for screening for "activated" plasma. In hypertensive subjects, this index was shown to be higher than that of the normotensive subjects (61 plus or minus 2.4 SE, and 45 plus or minus 5 SE). The index… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
2

Year Published

1975
1975
1984
1984

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 0 publications
1
7
0
2
Order By: Relevance
“…This would appear inconsistent with the existence of a renin inhibitor in essential hypertension. It is, however, consistent with the data of Sambhi et al, 28 demonstrating an accelerated rate of A 1 production by renin in the presence of plasma from hypertensive subjects. They postulate the presence of a renin activator in the plasma of hypertensive subjects to account for this phenomenon.…”
Section: Discussionsupporting
confidence: 93%
“…This would appear inconsistent with the existence of a renin inhibitor in essential hypertension. It is, however, consistent with the data of Sambhi et al, 28 demonstrating an accelerated rate of A 1 production by renin in the presence of plasma from hypertensive subjects. They postulate the presence of a renin activator in the plasma of hypertensive subjects to account for this phenomenon.…”
Section: Discussionsupporting
confidence: 93%
“…Although the normal form of substrate is the major renin substrate form in all plasmas, the new forms of substrate may have a significant effect on the overall renin reaction in plasma because form III (Rf = 0.16) appears to lead to an accelerated rate of angiotensin production and form II (Rf = 0.35) decreases this rate. These new substrate forms may, therefore, possibly account for the altered kinetics of the renin reaction observed in some hypertensive states (13,14).…”
Section: Discussionmentioning
confidence: 99%
“…Received for publication 14 November 1977 and in revised form 27 March 1978. say underestimated the renin substrate concentration suggesting that other forms of renin substrate were present in these plasmas which could be cleaved by renin to generate angiotensin I, but did not crossreact with the antiserum produced against the renin substrate of normal plasma (2). The following study examines the various forms of plasma renin substrate in several clinical states associated with hypertension and in patients receiving agents known to stimulate renin substrate synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, there is increasing evidence in the literature for the existence of normally occurring renin inhibitors [ 14,[16][17][18][19][20]. Alternatively it has been suggested that in creased reactivity of exogenous renin in plasma of patients with essential hypertension may reflect the presence of a renin activator [21,22], If inhibitors or activators of renin are produced by the kidney, the results of the present study suggest that these factors are not produced, to a greater or lesser extent, by the ischemic kidney than by the nonconstricted contralateral kidney. Indeed, in patients with essential hypertension, we have found that PRR in renal venous and peripheral plasma does not differ [1], This does not necessarily refute the possibility that the kidney secretes a renin inhibitor.…”
Section: Discussionmentioning
confidence: 99%